2001
DOI: 10.1002/cne.1068
|View full text |Cite
|
Sign up to set email alerts
|

Projections of the pontine nuclei to the cochlear nucleus in rats

Abstract: In the cochlear nucleus, there is a magnocellular core of neurons whose axons form the ascending auditory pathways. Surrounding this core is a thin shell of microneurons called the granule cell domain (GCD). The GCD receives auditory and nonauditory inputs and projects in turn to the dorsal cochlear nucleus, thus appearing to serve as a central locus for integrating polysensory information and descending feedback. Nevertheless, the source of many of these inputs and the nature of the synaptic connections are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…The unmyelinated type II auditory nerve fibers, which carry information from the outer hair cells of the cochlea, terminate among the granule cells [11,22], but the myelinated type I fibers do not [23,51]. The GCD does receive nonauditory inputs, including projections from the somatosensory cuneate nucleus [216,219], the trigeminal nuclei [74], the vestibular system [25,26,84], and pontine nuclei [131]. Many of the inputs are in the form of mossy fiber endings [65,122,131,219] and at least some are immunoreactive to the neurotransmitter, glutamate [219].…”
Section: Microcneuronal Shellmentioning
confidence: 99%
“…The unmyelinated type II auditory nerve fibers, which carry information from the outer hair cells of the cochlea, terminate among the granule cells [11,22], but the myelinated type I fibers do not [23,51]. The GCD does receive nonauditory inputs, including projections from the somatosensory cuneate nucleus [216,219], the trigeminal nuclei [74], the vestibular system [25,26,84], and pontine nuclei [131]. Many of the inputs are in the form of mossy fiber endings [65,122,131,219] and at least some are immunoreactive to the neurotransmitter, glutamate [219].…”
Section: Microcneuronal Shellmentioning
confidence: 99%
“…In the IWB preparation, these latency values most likely correspond to disynaptic transmission (Babalian et al 1997(Babalian et al , 1999(Babalian et al , 2002. As both the AVCN cells extended their dendrites to the GCD and the PN input to GCD was shown to be excitatory (Ohlrogge et al 2001), the most probable mechanism of observed disynaptic EPSPs would be an excitation of the granule cells by PN projections and following excitatory action from granule cells to target cells. The large majority of other responses in the present study were IPSPs at longer latencies (5.3 ms and longer), suggesting the involvement of additional synaptic relays.…”
Section: Discussionmentioning
confidence: 92%
“…An additional or alternative mechanism for polysynaptic inhibition of pyramidal cells from PN may function through a cerebellum-like circuit of the DCN (reviewed in Oertel and Young 2004) and would include PN-GCD-carthweel cell-pyramidal cells synaptic pathway. Even if no PN endings were found in the layer 2 of the DCN containing granule cells (Ohlrogge et al 2001), such a pathway may function through granule cells in all other CN areas known to send parallel fibers to the DCN (Mugnaini et al 1980b). It should also be noted that additional synaptic relays in the GCD and/or within the magnocellular CN core, including, for example, Golgi cells, unipolar brush cells, interneurons, and CN cells projecting to the contralateral CN, may account for PNinduced responses with very long latencies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations